2015
DOI: 10.1002/anie.201500983
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Tricarbastannatranes and Their Reactivity in B(C6F5)3‐Promoted Conjugate Additions

Abstract: The synthesis and characterization of a series of tricarbastannatranes, in the solid state and in solution, are described. The structures of the complexes [N(CH2 CH2 CH2 )3 Sn](BF4 ), [N(CH2 CH2 CH2 )3 Sn](SbF6 ), [N(CH2 CH2 CH2 )3 Sn]4 [(SbF6 )3 Cl], and [(N(CH2 CH2 CH2 )3 Sn)2 OH][MeB(C6 F5 )3 ] were determined by X-ray crystallography. Furthermore, the B(C6 F5 )3 -promoted conjugate addition of alkyl-tricarbastannatranes to benzylidene derivatives of Meldrum's acid was investigated, and detailed mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Our design employs the atrane‐type framework [31] and brings three benefits for the establishments of heavier group 14 cation‐based LSAs: 1) stabilization of the cationic center by the intramolecularly transannular N−E (E=Si, Ge, or Sn) bond, 2) orientation of the coordinated site of the cationic center by blocking one of the two apical vacant orbitals of the N−E bond, and 3) facile tuning of steric and electronic factors by changing the aromatic ligands. Although few works to isolate cationic atrane‐type molecules having a group 14 center were reported, [32–34] their use as hard and soft catalytic LSAs remains unexplored. Herein, we report the synthesis and catalytic activity of the atrane‐type molecules 1 E + (E=Si, Ge, or Sn) with a cationic group 14 center (Figure 1B).…”
Section: Figurementioning
confidence: 99%
“…Our design employs the atrane‐type framework [31] and brings three benefits for the establishments of heavier group 14 cation‐based LSAs: 1) stabilization of the cationic center by the intramolecularly transannular N−E (E=Si, Ge, or Sn) bond, 2) orientation of the coordinated site of the cationic center by blocking one of the two apical vacant orbitals of the N−E bond, and 3) facile tuning of steric and electronic factors by changing the aromatic ligands. Although few works to isolate cationic atrane‐type molecules having a group 14 center were reported, [32–34] their use as hard and soft catalytic LSAs remains unexplored. Herein, we report the synthesis and catalytic activity of the atrane‐type molecules 1 E + (E=Si, Ge, or Sn) with a cationic group 14 center (Figure 1B).…”
Section: Figurementioning
confidence: 99%
“…[11,12] Thetransannular N-Sn interaction in the carbastannatrane backbone selectively activates its apical substituent, which facilitates the transfer of alkyl groups that are otherwise unactivated towards transmetallation. [13,14] Enantioenriched alkylcarbastannatranes can also be stored indefinitely under ambient conditions without erosion of enantiopurity.D uring product isolation, tin byproducts from carbastannatranes are easily removed by standard column chromatography.T hus,a lkylcarbastannatrane reagents have tremendous potential for broad application as isolable sources of stereodefined alkyl nucleophiles in organic synthesis.H erein, we report the use of isolable primary and secondary alkylcarbastannatrane nucleophiles in site-specific fluorination reactions.These reactions occur without the need for transition metal catalysis or in situ activation. When enantioenriched alkylcarbastannatranes are employed, fluorination occurs predominately via as tereoinvertive mechanism to generate highly enantioenriched alkyl fluoride compounds.T hese conditions can also be extended to stereospecific chlorination, bromination, and iodination reactions.…”
Section: Incorporation Of Carbon-fluorine Bonds Into Drug Candidatesmentioning
confidence: 99%
“…We found that primary alkyl, secondary alkyl, and benzylic carbastannatrane derivatives could be successfully fluorinated (Scheme 4) under these conditions.Y ields generally fall within the range of 50-70 %w ith no concurrent formation of protodestannylated byproducts in any reaction. Due to the mild conditions of this reaction, sensitive functional groups such as alcohols (14), esters (13 and 20), boronate esters (15), and silyl ethers (21) are well tolerated. Fluorination of an oxygen-containing heterocycle (19)a lso proceeded smoothly.S econdary alkylcarbastannatrane derivatives consistently undergo fluorination reactions within minutes at RT,while primary derivatives tend to require slightly longer reaction times (ca.…”
mentioning
confidence: 99%